Factors influencing the reproducibility of isokinetic knee flexion and extension test findings - Alt, T.; Knicker, A. J.; Strüder, H. K. (Isokinetics and Exercise Science, 2014)
Although the reliability of isokinetic strength tests of knee flexors (flex) and extensors (ext) has been examined several times, statistical evidence about the influence of internal and external factors is missing. OBJECTIVE: This study aims to examine the impact of familiarisation, muscle group, contraction mode, angular velocity and test parameters on the reproducibility of findings derived from an isokinetic dynamometer (IsoMed 2000). METHODS: Thirty-three male subjects (mean age: 22.3 years) with no prior experience of isokinetic exercise participated in three identical test sessions (T1, T2, T3), each separated by 48-72 h. Peak moment (PM), angle of peak moment (APM) and contractional work (CW) were determined unilaterally (left and right) during maximum concentric (con) and eccentric (ecc) knee flexion (abdominal position) and extension (supine position) at 30, 90 and 150°/s, respectively. An ANOVA with repeated measures confirmed systematic bias. Reproducibility of consecutive tests (T1-T2, T2-T3) was assessed by calculating the intra-class correlation coefficient (ICC 2,1) (relative reliability) as well as the standard error of measurement (SEM) (absolute reliability). ICC values were averaged according to respective factors (Fisher's z-transformation) and tested for significant differences by Steiger's formulas. RESULTS: PM and CW demonstrated a high absolute reliability (SEM: 4.7-10.5%). Relative reproducibility varied considerably (p<= 0.05) between muscles (ecc flex > ecc ext), contraction modes (con ext > ecc ext) and test parameters (PM=CW > APM), but did not depend on angular velocity (30=90=150°/s). Due to familiarisation the reliability of PM obtained from eccentric knee extensions significantly increased (T2-T3 > T1-T2). CONCLUSIONS: These results improve the development and execution of reliable isokinetic strength testing protocols for unilateral knee flexion and extension together with the interpretation of different test parameters.